Boron doped silver-copper alloy nanoparticle targeting intracellular S. aureus in bone cells - Tahir Abdulrehman (8697696) (2020)
Objectives Alloyed metallic nanoparticles of silver and copper are effective against intracellular infection. However, systemic toxicity may arise due to the non-specific delivery of the nanoparticles. In addressing the issue, this study deals with the targeting of silver-copper-boron (ACB) nanoparticles to infected osteoblasts, which could decrease systemic toxicity and form the basis of targeting specific markers expressed in bone infections. Methods ACB nanoparticles were synthesized and conjugated to the Cadherin-11 antibody (OBAb). The effect of targeting nanoparticles against extracellular and intracellular S. aureus was determined by enumeration of bacterial growth. The binding of the targeting nanoparticles to infected osteoblasts as well as the visualization of live/dead bacteria due to treatment was carried out using fluorescence microscopy. MTT assay was used to determine the viability of osteoblasts with different concentrations of the nanoparticles. Results The ACB nanoparticles conjugated to OBAb (ACB-OBAb) were effective against extracellular S. aureus. The ACB-OBAb nanoparticles showed a 1.32 log reduction of intracellular S. aureus at a concentration of 1mg/L. The ACB-OBAb nanoparticles were able to bind to the infected osteoblast and showed toxicity to osteoblasts at levels ≥20mg/L. Also, the percentage of silver, copper, and boron in the nanoparticles determined the effectiveness of their antibacterial activity. Conclusion The ACB-OBAb nanoparticles were able to target the osteoblasts and demonstrated significant antibacterial activity against intracellular S. aureus. Targeting shows promise as a strategy to target specific markers expressed on infected osteoblasts for efficient nanoparticle delivery, and further animal studies are recommended to test its efficacy in vivo. Other Information Published in: PLoS ONE License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1371/journal.pone.0231276